2017
DOI: 10.12688/f1000research.11363.1
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in understanding Listeria monocytogenes infection: the importance of subcellular and physiological context

Abstract: The bacterial pathogen Listeria monocytogenes ( Lm) is the causative agent of listeriosis, a rare but fatal foodborne disease. During infection, Lm can traverse several host barriers and enter the cytosol of a variety of cell types. Thus, consideration of the extracellular and intracellular niches of Lm is critical for understanding the infection process. Here, we review advances in our understanding of Lm infection and highlight how the interactions between the host and the pathogen are context dependent. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 93 publications
(112 reference statements)
1
13
0
Order By: Relevance
“…We noted the presence of multiple bacteria intracellularly in a single cell which can be caused by multiple invading events or by intracellular replication of the bacteria, as shown previously in Caco-2 cells (Kanki et al, 2018). Upon cell invasion, L. monocytogenes can alter host cell actin distribution (Kuhbacher et al, 2015;David and Cossart, 2017;Radoshevich and Cossart, 2018), which was observed in our study by a lower abundance of actin in the brush border of infected cells. Additionally, a remarkable difference in bacterial translocation between proximal and distal monolayer cultures was observed, with a higher microbial translocation through distal epithelium.…”
Section: Discussionsupporting
confidence: 86%
“…We noted the presence of multiple bacteria intracellularly in a single cell which can be caused by multiple invading events or by intracellular replication of the bacteria, as shown previously in Caco-2 cells (Kanki et al, 2018). Upon cell invasion, L. monocytogenes can alter host cell actin distribution (Kuhbacher et al, 2015;David and Cossart, 2017;Radoshevich and Cossart, 2018), which was observed in our study by a lower abundance of actin in the brush border of infected cells. Additionally, a remarkable difference in bacterial translocation between proximal and distal monolayer cultures was observed, with a higher microbial translocation through distal epithelium.…”
Section: Discussionsupporting
confidence: 86%
“…The rapid and robust release of DNA observed may serve MCs, which display low phagocytic capacity, 34,35 the ability to inhibit bacterial multiplication alongside MC degranulation together with chemokine and cytokine secretion which is vital in driving neutrophil recruitment during L. monocytogenes infection, as suggested by Gekara and Weiss. 36 In our study, we confirmed that L. monocytogenes is killed by hMCs, while promoting hMC degranulation and the release of IL-8 and MCP-1, thus supporting the role of MC in the inflammatory process of cellular recruitment and bacterial clearance.…”
Section: Discussionmentioning
confidence: 96%
“…Listeria monocytogenes , a Gram-positive foodborne pathogen, can cause listeriosis and meningitis in immunocompromised individuals, and spontaneous abortions during pregnancy ( 59 , 60 ). Inside macrophages, L. monocytogenes can escape from the phagosome and proliferate in the cytosol (Figure 1 B) ( 61 ).…”
Section: Zebrafish Macrophage–bacteria Interactions In Vivomentioning
confidence: 99%